요양보호사의 직장폭력 경험실태 - 서은주(Seo, Eun ju); 김숙영(Kim, Souk Young) (Sŏngin Kanho Hakhoe chi, 2012)
Purpose: This is a descriptive research that reports incidents of workplace violence among care helpers. Methods: The subjects were 181 care helpers from elderly care facilities and domiciliary elderly welfare centers in Daejeon. Data were collected through self-administered questionnaires from July to November 2011. Subjects were asked to report incidents of violence within the previous six months. Data analysis included one-way ANOVA, and logistic regression analysis. Results: Forty-seven percent of care helpers reported verbal violence, 16% reported being physically threatened, more than 21 % reported sustaining a physical injury with 2% reporting severe physical injuries. Further, 18.8% of the care givers reported being sexually harassed by client. There were differences in reported workplace violence based on service types, service hours and whether there were policies about workplace violence. Conclusion: To prevent workplace violence for carehelpers, it is necessary to make a policy for preventing violence and develop a violence prevention program to meet service characteristics of facility-based and domiciliary care helpers.